The Termite Fecal Nest: A Framework for the Opportunistic Acquisition of Beneficial Soil Streptomyces (Actinomycetales: Streptomycetaceae) - Chouvenc, Thomas; Elliott, Monica L; Šobotník, Jan; Efstathion, Caroline A; Su, Nan-Yao (Environmental entomology, 2018)
Mutualistic associations between insects and microorganisms must imply gains for both partners, and the emphasis has mostly focused on coevolved host-symbiont systems. However, some insect hosts may have evolved traits that allow for various means of association with opportunistic microbial communities, especially when the microbes are omnipresent in their environment. It was previously shown that colonies of the subterranean termite Coptotermes formosanus Shiraki (Blattodea: Rhinotermitidae) build nests out of fecal material that host a community of Streptomyces Waksman and Henrici (Actinomycetales: Streptomycetaceae). These Actinobacteria produce an array of bioactive metabolites that provides a level of protection for termites against certain entomopathogenic fungi. How C. formosanus acquires and maintains this association remains unknown. This study shows that the majority of Streptomyces isolates found in field termite fecal nest materials are identical to Streptomyces isolates from soils surrounding the nests and are not vertically inherited. A survey of Streptomyces communities from C. formosanus fecal nest materials sampled at 20 locations around the world revealed that all nests are reliably associated with a diverse Streptomyces community. The C. formosanus fecal nest material therefore provides a nutritional framework that can recruit beneficial Streptomyces from the soil environment, in the absence of long-term coevolutionary processes. A diverse Streptomyces community is reliably present in soils, and subterranean termite colonies can acquire such facultative symbionts each social cycle into their fecal nest. This association probably emerged as an exaptation from the existing termite nest structure and benefits both the termite and the opportunistic colonizing bacteria.
Keywords: Feces; Isoptera; Symbiosis; Soil Microbiology; mužské pohlaví; ženské pohlaví; zvířata; feces; Antifungal Agents; půdní mikrobiologie; Female; Streptomyces; symbióza; Male; antifungální látky; Animals